Analisis Kalor Dan Sintesis Bioetanol Dari Serabut Kelapa Sawit Sebagai Alternatif Bahan Bakar Terbarukan - Arsyad, Arsyad; Diah, Anang Wahid M.; Said, Irwan (Jurnal Akademika Kimia, 2015)
Palm fibers are solid waste from the palm oil processing plant. Palm fibers can be used as an alternative fuels for traditional and modern (bioethanol). This study aims to determine the amount of heat generated from the burning of palm fibers, and determine the number of conversions of bioethanol from palm fibers through the fermentation techniques. In this study used a bomb calorimeter is determine heat value and apply through fermentation using saccharomyces cereviseae in various times of 5 and 11 days to synthesis ethanol. The step in this study were sample preparation, delignification, hydrolysis with acid variation, and fermentation. Determination of bioethanol content from the fermentation was analysed using ethanol sensor. The heat value of palm fibers is equal to 4708.21 cal/g and the highest ethanol fermented product obtained on days 11, ie 5.23%. It can be concluded that palm fibers can be used potentially as an alternative renewable fuels to substitute coal or diesel power.